Implementation of Blended Learning in the Pandemic Period of Arabic Subjects in MTs Negeri 1 Banyumas (International Journal of Scientific Research and Management (IJSRM), 2022)
Learning Arabic in MTs Negeri 1 Banyumas many encountered various obstacles and obstacles. in the midst of this Covid-19 condition. Using the blended learning model by combining online learning and face-to-face learning (offline) in the Covid-19 pandemic can increase the effectiveness of learning and the learning spirit of learners because in addition to getting online subject matter also still get direct assistance from teachers in the teaching and learning process by paying attention to strict health protocols. This research is qualitative descriptive research because it produces qualitative data. Data collection uses interview, observation and documentation models. Analytical techniques using description techniques with Miles and Huberman’s interaction analysis model with flow include data collection, data reduction, data presentation and conclusion withdrawal. The results of the study concluded, the first blended learning planning of Arabic MTs Negeri 1 Banyumas includes preparing a Learning Implementation Plan (RPP) and preparation of facilities and infrastructure supporting blended learning. Blended learning in Arabic subjects in MTs Negeri 1 Banyumas in this pandemic period is carried out with a provision of one day of online learning and one day of offline learning with a maximum capacity of 20 learners per class with a duration of 30 minutes per meeting hour. The learning evaluation system includes self-assessment, UTS or UAS that have been compiled by teachers using googleform and voice notes.